A new method for spectrophotometric determination of carbaryl based on rubber tree bark peroxidase enzymatic reaction - Sam ang Supharoek (2018)
© 2018 Elsevier B.V. A method for the determination of carbaryl in vegetable samples was developed employing peroxidase enzyme extracts from newly excised rubber tree bark strips as a catalyst. The solid phase extraction method QuEChERS was utilized for sample preparation followed by dispersive liquid-liquid microextraction (DLLME) to increase the concentration of the analyte before analysis by UV–Visible spectrophotometry. Parameters influencing this enzymatic development method and efficiency of DLLME were carefully studied. Under selected conditions, absorbance was in proportion to carbaryl concentration in the range of 0.1–3.0 mg L−1with linear regression (r2) of 0.9999. Limit of detection (LOD) and limit of quantitation (LOQ) were 0.06 mg L−1and 0.25 mg L−1, respectively. Relative standard deviation (RSD) values for the samples were 2.51–4.06% (n = 7). Good recoveries of carbaryl were obtained in the range of 83–118%. The proposed method proved rapid, reliable and selective for determination of carbaryl in vegetable samples.